2013
DOI: 10.5539/enrr.v3n4p46
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Depredation by Carnivores in the Serengeti Ecosystem, Tanzania

Abstract: Data for livestock depredation by wild animals were collected in villages outside Serengeti National Park, northern Tanzania. We tested livestock mortality against distance of the villages from the protected area in relation to carnivore species involved, methods used to protect livestock from being depredated and frequency of livestock diseases. The results indicate that distance from the park significantly influenced livestock depredation with the lowest depredation rates in the villages farthest away. Spott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, conflicts with wildlife near these protected areas impose livelihood costs and contribute to household food insecurity. Attacks by predators on people (Packer et al, 2005) and livestock (Holmern et al, 2007; Røskaft et al, 2013), as well as crop depredation (Gillingham & Lee, 2003; Kaswamila et al, 2007), are frequent. Such conflicts inflict direct economic losses on livestock keepers and farmers, in addition to the opportunity costs of labour devoted to guarding herds and fields.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, conflicts with wildlife near these protected areas impose livelihood costs and contribute to household food insecurity. Attacks by predators on people (Packer et al, 2005) and livestock (Holmern et al, 2007; Røskaft et al, 2013), as well as crop depredation (Gillingham & Lee, 2003; Kaswamila et al, 2007), are frequent. Such conflicts inflict direct economic losses on livestock keepers and farmers, in addition to the opportunity costs of labour devoted to guarding herds and fields.…”
Section: Introductionmentioning
confidence: 99%
“…Guarding is one of the good livestock husbandry practices followed by keeping under shelter as informed by most household survey and focus group participants as an effective preventative measure to reduce livestock depredation and deescalate the human‐carnivore conflict. Angela et al (2013) reported that guarding of livestock herds used to defend livestock from predators reduces the rate of depredation in African landscapes. Guarding livestock and keeping them under shelter, particularly at night, was a common method in Northern Tanzania to reduce livestock attacks (Hariohay & Roskaft, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…;Lichtenfeld et al (2015) have strategies are distinctive among localities. Guarding is one of the good livestock husbandry practices followed by keeping under shelter as informed by most household survey and focus group participants as an effective preventative measure to reduce livestock depredation and deescalate the human-carnivore conflict Angela et al (2013). reported that guarding of livestock herds used to defend livestock from predators reduces the rate of depredation in African landscapes.…”
mentioning
confidence: 99%
“…In addition, livestock keepers use traditional techniques and weapons such as a machete ( panga ), bow and arrow, and spears to defend their cattle against attacks by dangerous animals. In the Serengeti Ecosystem retaliatory killing by livestock keepers has been implicated in the extirpation of African wild dogs ( Lycaon pictus ) [72, 73].…”
Section: Discussionmentioning
confidence: 99%